Tectonic and Lithological Influences on Fracturing in a Cenozoic Carbonate System: Implications for Reservoir Quality Development - Munroe, Mary K. (Curtin University, 2015)
Carbonate reservoirs make up over 60 per cent of the world’s oil and 40 per cent of the world’s gas reserves. The development of fractures in the carbonate reservoirs within the Elk and Antelope petroleum field, Papua New Guinea, is complex and varied. Fracture forming processes, original depositional rock fabric, and subsequent diagenesis all affect the micro/macroscale development of fractures and reservoir quality. These factors are examined in this thesis.